Blithe spirit [videorecording (DVD)] - Moorcroft, Nick, 1979-; Leonard, Meg; Ashworth, Piers; Stevens, Dan, 1982-; Mann, Leslie, 1972-; Fisher, Isla, 1976-; Dench, Judi, 1934-; Coward, Noël, 1899-1973 (Shout! Factory, 2021)
Best selling crime novelist Charles suffers from terrible writer's block and is struggling to finish his first screenplay. His picture-perfect new wife Ruth is doing her best to keep him focused so they can fulfill her dream of leaving London for Hollywood. Charles' quest for inspiration leads him to invite the eccentric mystic Madame Acarti to perform a séance in his home. He gets more than he bargained for when Madame Acarti inadvertently summons the spirit of his first wife: the brilliant and fiery Elvira. Ready to pick up her life right where she left off, Elvira is shocked to discover the prim and proper Ruth is now married to her husband and running her household. Charles finds himself stuck between his two wives and their increasingly over-the-top attempts to outdo one another.